Corporate Criminal Liability in the Indonesian Criminal Law System - Romauli Sirait; Ghufron Ghufron; Cedatendo Lambang Provisky (Budapest International Research and Critics University, 2022)
The issue of corporate responsibility is still a matter of debate even though several laws outside the Criminal Code have listed corporations as the subject of criminal acts. This relates to the principle of error (geen starf zonder schuld), limits of ability to be responsible and forms of criminal responsibility. The research method used is a literature study research system where research is carried out by searching, reading, recording and analyzing findings in the field related to written sources such as books, journals, archives, articles or magazines that have a correlation with the problem being studied. In the socio-cultural field, corporate criminal acts are carried out in the form of actions that are detrimental to copyright holders, brands; not paying attention to the safety and health of workers/laborers; criminal acts that result in damaging education and the younger generation such as narcotics and psychotropic abuse and so on. In the Indonesian Criminal Code (KUHP), there is no known criminal provision that stipulates an artificial legal subject (rechtpersoon) or corporation, as a subject that can be subject to a crime. This can be seen in the general provisions of the Criminal Code which state that Indonesian laws and regulations apply to everyone.